A Comparative Study on Toxicity of Recombinant Chitinase on A Polyphagous Pest, Helicoverpa Armigera: Life Sciences-Biotechnology for Prospective Medical Science - Esther Shoba R (International Journal of Life Science and Pharma Research, 2022)
Holometabolous insects complete their life cycle in four stages: egg, larva, pupa and adult. The larval stage is characterized by instar and on an average most larvae has 4- 6 instar stages that occurs between molts. One of the essential enzyme for the process of moulting is chitinase. Expression of chitinase gene takes place when the insect is ready to moult, wherein the old exoskeleton being made of chitin is replaced with the new exoskeleton. Reports indicate that the introduction of the chitinase enzyme at inappropriate time and at inappropriate concentration will prevent the formation of chitin, resulting in no moult, thus growth retardation of the insect and finally death. Insects own chitinase has shown to be a potential insecticide. In the present study, gene encoding for Helicoverpa armigera chitinase was isolated and the sequence was found to be of 1734bp as compared to the reference sequence. The gene was expressed in a prokaryotic and eukaryotic host system. The protein was purified using Ni- NTA column as the protein was tagged with histidine. Chitinase activity was determined and the obtained enzyme was used for toxicity studies against the same insect. Injection assay, topical application and oral ingestion studies showed that Pichia pastoris expressed recombinant chitinase was more effective as compared to the Escherichia coli expressed recombinant chitinase. In case of injection assay, P. pastoris expressed recombinant chitinase recorded 77% mortality for the highest concentration used. Topical application showed 58% and 40% of malformed pupae for Pichia pastoris end E. coli expressed recombinant chitinase. An significant decrease in weight gain was observed on 2nd day for P. pastoris expressed recombinant chitinase and from 7th day for E.coli expressed recombinant chitinase in the oral ingestion studies. Effectiveness of Pichia pastoris expressed recombinant chitinase might be because of post translational modifications in the eukaryotic system.